Tools, frameworks and resources to guide global action on strengthening rural health systems: a mapping review - Dewi Retno Pamungkas; Belinda O'Sullivan; Matthew McGrail; Bruce Chater (BMC, 2023)
Abstract Background Inequities of health outcomes persist in rural populations globally. This is strongly associated with there being less health coverage in rural and underserviced areas. Increasing health care coverage in rural area requires rural health system strengthening, which subsequently necessitates having tools to guide action. Objective This mapping review aimed to describe the range of tools, frameworks and resources (hereafter called tools) available globally for rural health system capacity building. Methods This study collected peer-reviewed materials published in 15-year period (2005-2020). A systematic mapping review process identified 149 articles for inclusion, related to 144 tools that had been developed, implemented, and/or evaluated (some tools reported over multiple articles) which were mapped against the World Health Organization's (WHO's) six health system building blocks (agreed as the elements that need to be addressed to strengthen health systems). Results The majority of tools were from high- and middle-income countries (n = 85, 59% and n = 43, 29%, respectively), and only 17 tools (12%) from low-income countries. Most tools related to the health service building block (n = 57, 39%), or workforce (n = 33, 23%). There were a few tools related to information and leadership and governance (n = 8, 5% each). Very few tools related to infrastructure (n = 3, 2%) and financing (n = 4, 3%). This mapping review also provided broad quality appraisal, showing that the majority of the tools had been evaluated or validated, or both (n = 106, 74%). Conclusion This mapping review provides evidence that there is a breadth of tools available for health system strengthening globally along with some gaps where no tools were identified for specific health system building blocks. Furthermore, most tools were developed and applied in HIC/MIC and it is important to consider factors that influence their utility in LMIC settings. It may be important to develop new tools related to infrastructure and financing. Tools that have been positively evaluated should be made available to all rural communities, to ensure comprehensive global action on rural health system strengthening.